2014
DOI: 10.2147/prom.s49586
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up care for breast cancer survivors: improving patient outcomes

Abstract: BackgroundAppropriate follow-up care is important for improving health outcomes in breast cancer survivors (BCSs) and requires determination of the optimum intensity of clinical examination and surveillance, assessment of models of follow-up care such as primary care-based follow-up, an understanding of the goals of follow-up care, and unique psychosocial aspects of care for these patients. The objective of this systematic review was to identify studies focusing on follow-up care in BCSs from the patient’s and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
1
20
0
3
Order By: Relevance
“…22,37 There is one population-based cohort study with a median follow-up time of 6.6 years that reported stable or improved QOL in the 6 to 18 month post-treatment phase, which resulted in an absolute survival advantage of 4.9% for BCS. 11 This study suggests that interventions that promote self-management, which have been shown to improve QOL outcomes, offer the potential to improve the quality and quantity of survival for BCS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…22,37 There is one population-based cohort study with a median follow-up time of 6.6 years that reported stable or improved QOL in the 6 to 18 month post-treatment phase, which resulted in an absolute survival advantage of 4.9% for BCS. 11 This study suggests that interventions that promote self-management, which have been shown to improve QOL outcomes, offer the potential to improve the quality and quantity of survival for BCS.…”
Section: Resultsmentioning
confidence: 99%
“…4,12,[22][23][24]27 Fear of recurrence represents existential concerns, uncertainty related to prognosis, and perceived morbidity associated with advanced disease. Anxiety is closely related to fear of recurrence and follow-up surveillance visits but lack of adequate knowledge to manage symptoms, uncertainty about the predicted recovery trajectory, and information and access to resources will increase a woman's anxiety levels.…”
Section: Breast Cancer Survivor Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients are commonly provided written information; however, the extent to which they read and find the information useful is rarely assessed. Due to the continuously increasing demands of breast cancer survivorship care (I. Chopra & Chopra, ), it is necessary to test low‐cost, simple methods of disseminating information to patients.…”
Section: Discussionmentioning
confidence: 99%